PENGENDALIAN PERMUKIMAN DI SEMPADAN SUNGAI CILIWUNG KELURAHAN MANGGARAI JAKARTA SELATAN BERDASARKAN PERATURAN DAERAH DKI JAKARTA NOMOR 1 TAHUN 2012 TENTANG RENCANA TATA RUANG WILAYAH 2030: Residential Control On The Riverbank Of Ciliwung, Manggarai District, South Jakarta Based On Dki Jakarta Regional Regulation Number 1 Of 2012 Concerning The 2030 Regional Spatial Plan - Ricky Dwi Prasetyo; Meta Indah Budhianti (AMICUS CURIAE, 2025)
Settlements located in the river basin area are often found in some urban areas. These settlements are not far from standing on the border area of the river flowing, especially those that occur in residential settlements around the border area of the Ciliwung River. This problem has occurred for a long time, causing various effects felt by the community. Of course, because of these identification problems, whether the implementation of settlement control in the Ciliwung River Basin, Manggarai Village, South Jakarta City is by the Jakarta Regional Regulation No. 1 of 2012 regarding the 2030 Regional Spatial Plan and how the efforts of the South Jakarta Administration City government can be made against the establishment of buildings in the Ciliwung River basin area based on the Jakarta Regional Regulation No. 1 of 2012 concerning the 2030 Regional Spatial Plan. In answering these problems, this study is executed using the Normative Juridical method of Descriptive Analysis, sourced from secondary data made from primary law and secondary legal materials, which are analyzed qualitatively so that conclusions can be drawn deductively. According to result the research and the conclusion that the Ciliwung River border area does not comply with the Jakarta Regional Spatial Plan, and for now, it is impossible to arrange the area in the area because there is no location determination from BWSCC.